Keefektifan Pembelajaran IPA Menggunakan Model Complette Sentence Berbantu Card Terhadap Hasil Belajar Siswa Kelas III SDN Ngelowetan Kabupaten Demak - Saputra, Henry Januar; Arifin, Zaenal; Ferdiansa, Rezza Aldi (Universitas Pendidikan Ganesha, 2017)
This study aims to determine the effectiveness of learning science using Compelette Sentence learning model in terms of comparison the average result of learning and mastery learning material science of energy and its use. The research was conducted in SDN Ngelowetan on 17 to 21 April 2017. The method used in this research is to study the design of pretest-posttest control group design with a saturated sample. The instrument will involve a total of 20 multiple-choice test items. Method of collection using method of documentation and test method. Technique of data analysis done with mastery learn and t test. Results showed that the experimental and control groups on average there are differences in learning outcomes between students who get Complette Sentence learning model and students do not get the learning with the learning model Complette Sentence. Learning outcomes in the experimental group reached an average of 81.50 with the percentage of 86.67% mastery learning. While the average of learning outcomes in the control group was 75.18 with the percentage of mastery learning as much as 60.71%.